Hak Merek Dagang Persepektif Perundangan Dan Ekonomi Islam - Ach Bakir; Achmad Fageh (ITB AAS INDONESIA Surakarta, 2023)
One of the developments in the world of the Indonesian economy is the emergence of the issue of intellectual property rights or intellectual property, because it has become a standard regulation and there are laws. In Islamic teachings textually nothing mentions or explains this. In fact, if in Indonesia as actors or executors in increasing professionalism and productivity, then the study of intellectual property rights in the Indonesian legal system becomes something very important. This research is a type of library research, research whose object of study uses library data in the form of books as a data source. The results of this study are that trademark rights can be protected by law no. 20 of 2016 with the condition that the mark is registered at the Directorate General of Intellectual Property Rights, Ministry of Law and Human Rights. In Islamic economics, Hanafiyyah scholars do not recognize the existence of intellectual property, while the majority of scholars themselves recognize the existence of intellectual property because what is meant by property is anything of value and those who destroy it must bear the burden or the consequences